Cucurbits powdery mildew race identity and reaction of melon genotypes1 - Rabelo, Hudson De Oliveira [UNESP]; Santos, Lucas Da Silva [UNESP]; Diniz, Guilherme Matos Martins [UNESP]; Marin, Marcus Vinicius [UNESP]; Braz, Leila Trevisan [UNESP]; Mccreight, James Donald (Escola de Agronomia e Engenharia de Alimentos/UFG, 2017)
Genetic resistance is one of the most suitable strategies to control cucurbit powdery mildew (CPM) on melon, incited by Podosphaera xanthii or Golovinomyces orontii. However, many races of these pathogens have been reported worldwide in recent years, what may compromise the effectiveness of this method. Thus, annual surveys of CPM races and the screening of germplasm for new sources of genetic resistance provide a vital support to melon breeding programs. This study aimed at identifying a natural population of CPM race under greenhouse conditions, as well as evaluating the reaction of local and exotic melon germplasm for CPM-resistance. CPM race identity was based on the reaction of eight race differentials: Védrantais, Nantais Oblong, PMR 45, PMR 5, WMR 29, Edisto 47, PI 414723 and PI 124111. Fifty-nine melon genotypes were evaluated, 53 of them being germplasm accessions, and six net melon elite-inbred lines, besides two net melon-type cultivars (Louis and Fantasy). Plants were evaluated using a visual scale for leaf lesions. The causal pathogen was confirmed to be P. xanthii, based on the presence of fibrosin bodies in conidia and the complete resistance response of winter melon (Benincasa hispida). Race 4 was identified for the first time in the São Paulo state, Brazil. Genotypes A19, A30, A32, C67, C384, JAB-3, JAB-7, JAB-9, JAB-11, JAB-18, JAB-20 and Solarking showed to be resistant to the race 4.

O uso de resistência genética é um dos métodos mais adequados para o controle de oídio das cucurbitáceas em melão, causado por Podosphaera xanthii ou Golovinomyces orontii. Contudo, muitas raças desses patógenos têm sido descobertas, o que pode comprometer a eficácia desse método. Fazem-se, então, necessários o constante monitoramento de raças de oídio e a busca por novas fontes de resistência. Objetivou-se identificar em nível de raça uma população natural de oídio das cucurbitáceas em casa-de-vegetação, bem como avaliar a reação de genótipos locais e exóticos de meloeiro à raça identificada. A identificação da raça foi baseada na reação de oito linhagens diferenciadoras (PI 414723, PMR 45, PMR 5, WMR 29, Edisto 47, Nantais Oblong, PI 124111 e Védrantais). Foram avaliados 59 genótipos de meloeiro, sendo 53 destes acessos de germoplasma e seis linhagens de melão rendilhado, além de duas cultivares (Louis e Fantasy). As plantas foram avaliadas com base em escala visual para lesões nas folhas. A espécie P. xanthii foi confirmada como o agente causal, pela visualização de corpos de fibrosina nos conídios e pela resistência da abóbora d’água (Benincasa hispida). A raça 4 foi identificada pela primeira vez no estado de São Paulo. Os genótipos A19, A30, A32, C67, C384, JAB-3, JAB-7, JAB-9, JAB-11, JAB-18, JAB-20 e Solarking mostraram-se resistentes à raça 4.
Identificação de raças de oídio das cucurbitáceas e reação de genótipos de meloeiro
Keywords: Cucumis melo; Podosphaera xanthii; genetic resistance; physiologic races; Cucumis melo; Podosphaera xanthii; resistência genética; raças fisiológicas